Functional comparisonbetweenthe Constitutional Chamber of the union Supreme Court of the united arab Emiratesand the Constitutional council of the Republic of Kazakhstan in the constitutions of the two states - Abdul Wahab Abdul, H. E. (Право и государство, 2015)
In article is carried out comparative analysis of constitutional and legal status between The Constitutional Chamber of the Union Supreme Court of the United Arab Emirates and The Constitutional Council of the Republic of Kazakhstan. Author compares two mentioned bodies of constitutional review in the scope of their functional role through the following aspects: appointment of the members, the competence, immunities of the members, the power and effectiveness of decisions and provisions.
Keywords: constitutional review; body of constitutional review; constitutional guarantees; judicial chamber; Research Subject Categories::LAW/JURISPRUDENCE